2017
DOI: 10.1111/jre.12511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combined use of enamel matrix derivative and atelocollagen sponge scaffold on osteoblastic differentiation of mouse induced pluripotent stem cells in vitro

Abstract: These data suggest that combining ACS with EMD increases levels of osteoblastic differentiation and mineralization in miPS-EB-derived cells, compared with ACS used alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…It is important to note that PTH treatment had no significant effect on the expression of Bglap, one of the key osteoblastic markers. A similar result was obtained in a previous study by our research group, 13 in which we investigated the effects of EMD on the miPS-EB-derived into intracellular compartments 38 and recycled to the membrane, causing receptor re-sensitization. 39 Once these complexes are targeted for degradation, receptor down regulation is observed.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It is important to note that PTH treatment had no significant effect on the expression of Bglap, one of the key osteoblastic markers. A similar result was obtained in a previous study by our research group, 13 in which we investigated the effects of EMD on the miPS-EB-derived into intracellular compartments 38 and recycled to the membrane, causing receptor re-sensitization. 39 Once these complexes are targeted for degradation, receptor down regulation is observed.…”
Section: Discussionsupporting
confidence: 85%
“…Zujur et al 33 reported that, in comparison with 2D conditions, the 3D-cultured miPSC-derived mesodermal cells exhibited accelerated osteogenic differentiation, giving rise to functional osteoblast-osteocyte populations within calcified structures. Moreover, in our previous study, 13 we showed that combining EMD with ACS enhanced osteoblastic differentiation and mineralization in miPS-EB-derived cells. Taking these into consideration, the accelerated outcomes we observed might be due to the synergetic effects of the intermittent PTH treatment and the scaffold-based 3D culture system.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These phenomena were similar to the finding that an artificial collagen sponge implanted in the extraction socket promotes the differentiation and proliferation of mesenchymal stem cells and provides a scaffold for bone formation. 40,41 Recently, tissue activation by PBMT was shown to be strongly associated with mitochondrial adenosine tri-phosphate (ATP) production facilitated by cytochrome C oxidase, but the precise effects of the laser wavelengths used in the present study remain to be clarified.…”
Section: Discussionmentioning
confidence: 94%